Physiological concepts in physical education and sports training: stress, homeostasis and allostasis - Benedito Pereira; Tácito Pessoa de Souza Junior (Universidade Federal de Santa Catarina, 2008)
The objective of this review article is to discuss the concepts of stress and homeostasis (homeos = equal; stasis = stable) and to expose their limitations on the basis of recent evidence demonstrating that the supposed internal stability of living organisms is merely apparent, and is even independent of environmental factors. This internal instability is often observed by researchers investigating circadian rhythms (hormone secretion), temporal series (heart rate) and behavior (hunger and satiety), who argue in favor of substituting the theory of homeostasis by the concept of allostasis (allo = different; stasis = stable). Indeed, these researchers suggest that the objective of regulation and control is not stability. There are two consequences for Physical Education and Sport if allostasis is accepted as a physiological paradigm: 1. Selye's concept of stress requires a new defi nition and interpretation, with a clear impact on the concept of load and overload; 2. Noakes' central governor hypothesis to explain the fatigue resulting from intense physical exercise loses its relevance, as will be discussed in this paper. Furthermore, it is very diffi cult for the model of stability by staying the same to explain why performance is improved by physical training or why we have a predisposition for this type of recognizedly anti-homeostatic activity. We intend to demonstrate the possibility that the allostatic concept of stability through change can explain these contradictions. Resumo O objetivo desta revisão é discutir criticamente os conceitos de estresse e homeostase (homeos = igual; stasis = constância) e expor suas limitações em função de recentes evidências que demonstram que a suposta estabilidade interna dos organismos vivos é apenas aparente, inclusive sendo independente de fatores ambientais. Essa instabilidade interna é freqüentemente constatada por pesquisadores dos ritmos circadianos (secreções hormonais), séries temporais (freqüência cardíaca) e comportamento (fome e saciedade), que argumentam a favor da substituição da teoria da homeostase pela noção de alostase (allo = diferente; stasis = constância). Na verdade, o propósito da regulação e controle segundo os mesmos não é a constância. Duas conseqüências para a Educação Física e Esporte com a aceitação da alostase como paradigma fisiológico são: 1. O conceito de estresse de Selye deve sofrer nova defi nição e interpretação, interferindo claramente na noção de carga ou sobrecarga de trabalho e, 2. A hipótese do governo central de Noakes na explicação da fadiga decorrente do exercício físico intenso perde o sentido, como será discutido neste trabalho. Além disso, é muito difícil explicar através da estabilidade pela constância como o desempenho é alterado pelo treinamento físico e porque temos predisposição para esse tipo de atividade reconhecidamente anti-homeostática. Pretendemos neste trabalho mostrar, portanto, a possibilidade de que com a noção de estabilidade pela mudança da alostase essas contradições perdem o sentido.